Fluid Balance After Tumescent Infiltration: A Practical Guideline to Avoid Dilution Anemia in Circumferential Liposuction Based on a Prospective Single-Center Study. (29th December 2022) - Aslani, Alexander; Waked, Karl; Kuenlen, Anian
Abstract: Background: Circumferential liposuction may cause dilution anemia due to a high volume of infiltrated tumescent. Studies analyzing the percentage of absorbed tumescent and the safe limit of tumescent infiltration are currently lacking. Objectives: The aim of this study was to calculate the average volume uptake of administered fluids in power-assisted liposuction, and to calculate a practical formula to determine the amount of fluid that can safely be administered without inducing symptomatic dilution anemia or hypervolemia. Methods: Patients undergoing circumferential liposuction with power-assisted tumescent infiltration were included in a prospective clinical study. All relevant administered and excreted volumes during and after the operation were collected. Preoperative vs postoperative hemogram results were compared and the hemodynamic parameters were followed for 24 hours. The average volume uptake was calculated based on the measured volumes, and on the ratio between administered volumes and the patient's blood volume. Results: Thirty patients were included during September 2021. The average volume uptake was 58% for a calculated 1.11:1 infiltration to aspiration ratio. There was a mean drop of 1.9 g/dL and 4.6% for the postoperative hemoglobin and hematocrit, respectively, with a stable red blood cell level. All patients remained hemodynamically stable without the need for blood transfusion or prolonged oxygen administration. The average tumescent vs blood volume ratio was 85.0%. Conclusions: In circumferential liposuction with power-assisted infiltration, the infiltrated tumescent volume should remain below 85% of the patient's blood volume to minimize the risk of symptomatic dilution anemia or hypervolemia. Level of Evidence: 4: